The Relationship between Psychological Well-Being and Self-Directed Learning in Medical Students - Izdihara, Anifa; Khoiriyah, Umatul (IIUM Medical Journal Malaysia, 2025)
Introduction: Student well-being plays a crucial role in influencing self-directed learning (SDL), particularly among medical students who face intense academic demands. This study aimed to assess the levels of psychological well-being and SDL among undergraduate students at the Faculty of Medicine, Universitas Islam Indonesia (FM UII), and to examine the relationship between the two variables. Materials and Methods: An observational, cross-sectional study design was employed, involving 317 undergraduate medical students from FM UII. Data collection utilized the Indonesian versions of Ryff’s Psychological Well-Being Scale and the Self-Directed Learning Readiness Scale. Univariate and bivariate analyses were conducted to evaluate the data and determine correlations. Results: Findings revealed that most students demonstrated moderate to high psychological well-being. SDL levels were predominantly high, with 74.8% of respondents reporting a high level of SDL, 25.2% reporting a moderate level, and none reporting low SDL. A statistically significant positive correlation was identified between psychological well-being and SDL (p=0.000; r=0.352), indicating a moderate relationship. Conclusion: The results suggest that most medical students at FM UII possess good psychological well-being and strong SDL readiness. A positive correlation between psychological well-being and SDL indicates that students with higher well-being are more likely to be confident and proactive in managing their own learning. These findings highlight the importance of fostering a supportive academic environment that prioritizes student mental health to enhance SDL capabilities. Faculty and educators should therefore integrate strategies that promote psychological well-being to improve learning outcomes